Reaping Digital Dividends : Leveraging the Internet for Development in Europe and Central Asia - Kelly, Tim; Liaplina, Aleksandra; Tan, Shawn W.; Winkler, Hernan (Washington, DC: World Bank, 2017)
From East to West, the economies of Europe and Central Asia (ECA) are not taking full advantage of the internet to foster economic growth and job creation. The residents of Central Asia and the South Caucasus pay some of the highest prices in the world for internet connections that are slow and unreliable. In contrast, Europe enjoys some of the world’s fastest and affordable internet services. However, its firms and individuals are not fully exploiting the internet to achieve higher productivity growth as well as more and better jobs. Reaping Digital Dividends investigates the barriers that are holding back the broader adoption of the internet in ECA.